THE EFFECT OF CINNAMON EXTRACT ON PERFORMANCE IMPROVEMENT AND ACCELERATION OF FATIGUE RECOVERY PROCESS IN WEIGHTLIFTING ATHLETES - Fahmi Hasan, Muhamad
Cinnamon is known to increase the acceleration of fatigue recovery, however testing on athletes is still limited, especially on athletes who have anaerobic characteristics such as weight lifters. On the other hand, excessive and prolonged levels of fatigue have an impact on increasing the risk of injury to athletes. Injury is the thing most athletes avoid, including weight lifters. Injuries can have an impact on a decrease in athlete's performance and career in reaching the peak of achievement. The purpose of this study was to analyze the effectiveness of kayu manis in accelerating the athlete's recovery process with indicators of Creatine Kinase (CK), C-Reactive Protein (CRP), lactic acid levels and other supporting indicators such as body composition and performance tests. The research design used was a two-way crossover with the treatment of each group for 8 weeks. The research subjects consisted of 48 athletes with an average age of 24,8 ± 4,2 years, training duration of 15,5 ± 2,4 years, height of 152,9 ± 2,1 cm, and body weight of 71,4 ± 5,2 kg. Subject selection criteria included weightlifting athletes who had at least one year's training experience and had participated in national weightlifting championships. The research variables measured in this study were recovery as shown by the level of CK, CRP and lactate, while performance variable was measured by clean and jerk and snatch competition simulations, and body composition variables was measured by lean mass, fat mass and fat free mass. The results of the study in the cinnamon group showed that there was an accelerated recovery process as indicated by a significant decrease of the CK, CRP and lactate when compared to the placebo group. This was demonstrated by the results of group x time value of 0.0005, showing significance in the effectiveness of accelerating the recovery process. The results of the study on performance variables as measured by clean and jerk and snatch found that there was no significant difference between the cinnamon group and the placebo group, as indicated by the group x time calculation results of 0.708 and 0.875, respectively. Results on the body composition variable showed no significant difference between the cinnamon and placebo groups for lean mass, fat mass, and total mass, shown by the respective group x time values of 0.174, 0.474, and 0.116. Overall the results of this study indicate that cinnamon has a significant and effective impact on accelerating the recovery process compared to placebo, but is not yet effective in increasing performance and improving body composition. For further research, testing can be carried out on sports with aerobic characteristics to complement testing on other characteristics of physiology sports.